Clinical aspects of functional dyspepsia and efficacy of ganaton (itopride hydrochloride) - V. T. Ivashkin; A. A. Sheptulin; A. S. Trukhmanov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Studying of clinical pattern of functional dyspepsia (FD) and efficacy of ganaton (itopride hydrochloride) in its treatment.Material and methods. Overall 509 patients with FD were investigated. Before and after 4-week course of ganaton (itopride hydrochloride) 50 mg tid, severity of clinical symptoms was estimated by 4-point system.Results. High frequency of combination of FD to nausea, symptoms of gastroesophageal reflux disease (heartburn) and irritable bowel syndromes (meteorism, disorders of defecation) was marked. Application of ganaton promoted relief of complaints in 46,6% of patients, significant decrease of their severity – at 47,8%.Conclusions. Ganaton is efficient agent in treatment of FD and concomitant functional disorders of gastro-intestinal tract.